Modular group and modular forms - Schmidt, Eric, author; Hulpke, Alexander, advisor; Achter, Jeff, committee member; Cavalieri, Renzo, committee member; Harton, John, committee member (Colorado State University. Libraries, 2010)
We prove some results about the structure of SL2(Z) and related groups. We define modular forms for this group and develop the basic theory. We then use the theory of lattices to construct examples of modular forms.
Covers not scanned.
Keywords: Modular groups; Forms, Modular